A reluctant belle - White, Beth, 1957- (Daughtry house, 2019)
"With the Civil War over, Mississippi Belle Joelle Daughtry wants to establish a school to teach freed slaves. But she might have to form an alliance with her childhood nemesis and reveal her deepest secret to make changes in her world--and her heart"--